Dual treatment with atazanavir–ritonavir plus lamivudine versus triple treatment with atazanavir–ritonavir plus two nucleos(t)ides in virologically stable patients with HIV-1 (SALT): 48 week results from a randomised, open-label, non-inferiority trial. Issue 7 (July 2015) - Perez-Molina, José A; Rubio, Rafael; Rivero, Antonio; Pasquau, Juan; Suárez-Lozano, Ignacio; Riera, Melcior; Estébanez, Miriam; Santos, Jesús; Sanz-Moreno, José; Troya, Jesús; Mariño, Ana; Antela, Antonio; et al.
Summary: Background: Problems associated with lifelong antiretroviral therapy, such as need for strict adherence, drug-related toxic effects, difficulties with treatment schedules, and cost, mean that simplification strategies should be sought. We aimed to explore the efficacy and safety of dual treatment with atazanavir–ritonavir plus lamivudine as an option to switch to from standard combination antiretroviral therapy in patients with an HIV-1 infection who are virologically suppressed. Methods: In this randomised, open-label, non-inferiority trial, we recruited patients aged 18 years and older with chronic HIV-1 infection and no previous treatment failure or resistance, and with HIV-1 RNA of less than 50 copies per mL for at least 6 months, negative hepatitis B virus surface antigen, and good general health, from 30 hospitals in Spain. Exclusion criteria were switch in antiretroviral therapy during the previous 4 months, previous virological failure, pregnancy or breastfeeding, Gilbert's syndrome, use of contraindicated drugs, grade 4 laboratory abnormalities, and previous intolerance to any of the study drugs. We randomly assigned patients (1:1; stratified by active hepatitis C virus infection and previous treatment; computer-generated random number sequence) to dual treatment with oral atazanavir (300 mg once daily) and ritonavir (100 mg once daily) plus lamivudine (300 mg once daily) or triple treatment with oral atazanavir (300 mg once daily) and ritonavir (100 mg once daily) plus two nucleos(t)ide reverse transcriptase inhibitors at the discretion of the investigators. The primary endpoint was virological response, defined as HIV-1 RNA of less than 50 copies per mL at week 48, in the per-protocol population, with a non-inferiority margin of 12%. We included patients who received at least one dose of the study drug in the safety analysis. This study is registered atClinicalTrials.gov, numberNCT01307488 . Findings: Between Sept 29, 2011, and May 2, 2013, we randomly assigned 286 patients (143 [50%] to each group). At week 48 in the per-protocol population, 112 (84%) of 133 patients had virological response in the dual-treatment group versus 105 (78%) of 135 in the triple-treatment group (difference 6% [95% CI −5 to 16%), showing non-inferiority at the prespecified level. 14 (5%) patients developed severe adverse events (dual treatment six [4%]; triple treatment eight [6%]), none of which we deemed related to the study drug. Grade 3–4 adverse events were similar between groups (dual treatment 77 [55%] of 140; triple treatment 78 [55%] of 141). Treatment discontinuations were less frequent in the dual-treatment group (three [2%]) than in the triple-treatment group (ten [7%]; p=0·047). Interpretation: In our trial, dual treatment was effective, safe, and non-inferior to triple treatment in patients with an HIV-1 infection who are virologically suppressed who switch antiretroviral therapy because of toxic effects, intolerance, or simplification. This combination has the potential to suppress some of the long-term toxic effects associated with nucleos(t)ide reverse transcriptase inhibitors, preserve future treatment options, and reduce the cost of antiretroviral therapy. Funding: Bristol Myers-Squibb and Fundación SEIMC-GESIDA.